The sarape of Saltillo: from textile to architecture - Dávila del Bosque, Argelia Isabel (UNIVERSIDAD DE SONORA, 2023)
This research is part of a doctoral project and aims to deepen the study of the sarape garment from different aspects; by defining the iconography of the sarape found in the garment as a symbol and its derivation to the graphic application in the houses of the Historic Center of Saltillo that were modified between 1880 and 1930, thanks to the technological advances of the time. All this, through theoretical research, as well as from the semiotic point of view to determine if this tangible and material record is transferred from a textile support to an architectural support that is reaffirmed as a symbol of Saltillo's identity. The methodological approach will be structured to achieve an approach and reflection from the theory of imaginaries and semiotics, as well as the use of the Panofsky method (1892-1968) for the visual analysis of the elements found. As a result of this reflection and study of the information collected, the visual, interpretative and analogical analysis of the components of the serape in relation to the architectural elements found in the selected houses is presented, thus deriving the use of the symbol as a resource of identity rescue in the architecture of the city of Saltillo.